Penerapan Media Pembelajaran Spin Edukasi (Roda Putar) Interaktif dalam Menanamkan Sikap Gotong Royong Siswa Kelas V B di SD Negeri 2 Meurandeh - Wina Sari Sihombing; Lhutfia Wahyu Safutri (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This research aims to examine the effectiveness of interactive spin education (spinning wheel) learning media in instilling cooperative attitudes in fifth grade students at SD Negeri 2 Meurandeh. This study uses a quantitative approach with a pre-experimental design, specifically one-group pretest-posttest design. The subjects of this research were 23 students of class V B SD Negeri 2 Meurandeh. Data collection was carried out using a Likert scale questionnaire consisting of 25 statements covering five dimensions: active student involvement, understanding of mutual cooperation material, teamwork and group discussion abilities, application of mutual cooperation values, and learning motivation and enthusiasm. Data were analyzed using descriptive statistics and paired sample t-test. The results showed that the average pretest score was 59.61 and the average posttest score was 93.70, with an average gain score of 0.860 which is in the high category. The paired t-test results showed a significance value of 0.000 < 0.05, meaning there is a significant difference between pretest and posttest scores. All five dimensions measured showed very effective criteria. The results prove that interactive spin education media is very effective in instilling cooperative attitudes in students and can be used as an innovative alternative in Pancasila Education learning.